2009
DOI: 10.1007/s00246-009-9412-7
|View full text |Cite
|
Sign up to set email alerts
|

Factor Analysis of Markers of Inflammation and Oxidation and Echocardiographic Findings in Children with a Positive Family History of Premature Coronary Heart Disease

Abstract: The objective of this study was to determine the predictive factor of a combination of traditional and new risk factors for coronary heart diseases (CHDs) as well as the echocardiographic findings in children of parents suffering premature myocardial infarction in comparison with controls. Overall, 239 adolescents aged 12 to 18 years including 112 children of parents with premature CHD (<55 years) and 127 age- and sex-matched controls without such a family history. In addition to measuring anthropometric index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…It is known that there is no detectable mRNA expression of pro-inflammatory cytokines in normal myocardial tissue, 37 but once cardiac injury sets in (such as with an MI), the intracardiac expression of IL-6, TNF-a and IFN-g mRNA expression possibly mediate the events of remodeling in the myocardium as reported earlier. [38][39][40][41][42] An increased expression of these cytokines may result in enhanced production of tissue repair molecules. Our results support this assumption, as myocardial mRNA expression of MMP-2, SDF-1 and TGF-b was significantly higher in chronic tobacco-exposed rats compared with tobacco-naïve rats with MI.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that there is no detectable mRNA expression of pro-inflammatory cytokines in normal myocardial tissue, 37 but once cardiac injury sets in (such as with an MI), the intracardiac expression of IL-6, TNF-a and IFN-g mRNA expression possibly mediate the events of remodeling in the myocardium as reported earlier. [38][39][40][41][42] An increased expression of these cytokines may result in enhanced production of tissue repair molecules. Our results support this assumption, as myocardial mRNA expression of MMP-2, SDF-1 and TGF-b was significantly higher in chronic tobacco-exposed rats compared with tobacco-naïve rats with MI.…”
Section: Discussionmentioning
confidence: 99%
“…Although most chronic conditions do not manifest until adulthood, an increasing number of studies indicate that children and adolescents with family histories of some conditions already show preclinical signs of these conditions (98). For example, children with a strong family history of coronary artery disease may show early signs of atherosclerosis, such as elevated markers of inflammation and plaque instability and increased carotid intima media thickness (4,39,93). However, the use of family history to assess the risk that children might develop chronic diseases as adults has not been thoroughly evaluated.…”
Section: Family History In Clinical Practicementioning
confidence: 99%
“…Indeed, it has been independently shown that individuals with a positive FH for CVD display higher levels of oxidative stress than the normal population (Kelishadi et al. ). Although the levels of antioxidant molecules were not determined and compared in this study, it can be hypothesized that this factor could have contributed to our findings.…”
Section: Discussionmentioning
confidence: 99%